Asymmetric Membranes Obtained from Sulfonated HIPS Waste with Potential Application in Wastewater Treatment - Marcial Alfredo Yam-Cervantes; Rita Sulub-Sulub; Mauricio Hunh-Ibarra; Santiago Duarte; Erik Uc-Fernandez; Daniel Pérez-Canales; Manuel Aguilar-Vega; Maria Ortencia González-Díaz (Membranes)
The recovery and reuse of high-impact polystyrene (HIPS) into high-value products is crucial for reducing environmental thermoplastics waste and promoting sustainable materials for various applications. In this study, asymmetric membranes obtained from sulfonated HIPS waste were used for salt and dye removals. The incorporation of sulfonic acid (-SO3H) groups into HIPS waste by direct chemical sulfonation with chlorosulfonic acid (CSA), at two different concentrations, was investigated to impart antifouling properties in membranes for water treatment. Asymmetric membranes from recycled HIPS, R-HIPS, R-HIPS-3, and R-HIPS-5 with 3 and 5% sulfonation degrees, respectively. Sulfonated HIPS shows a decrease in water contact angle (WCA) from 83.8° for recycled R-HIPS to 66.1° for R-HIPS-5, respectively. A WCA decrease leads to an increase in antifouling properties for R-HIPS-5, compared to non-sulfonated R-HIPS, which leads to a higher flux recovery ratio (FRR) and enhanced separation properties for sulfonated membranes. The HIPS-5 membrane exhibited the highest rejection rates for Reactive Black 5 dye (94%) and divalent salts (72% for MgSO4 and 67% for Na2SO4). The performance of the recycled HIPS asymmetric membranes is well correlated with porosity, water uptake, and the higher negative charge from the sulfonic acid groups present, which enhance the electrostatic repulsions of salts and dyes.